173 Seat belt fit and use behaviours observed among drivers aged 75+ years in their own vehicles. (1st September 2016) - Brown, Julie; Coxon, Kristy; Fong, Cameron; Clarke, Elizabeth; Rogers, Kris; Keay, Lisa
Abstract : Background: Older occupants are at increased risk of serious injury in a crash compared to younger occupants. While seatbelts reduce injury risk, effectiveness relies on good belt fit and positioning. Laboratory research indicates increased likelihood of poor belt fit with increasing age, however little is known about seat belt use in this age group. The aims of this work are to (i) describe belt fit and use among drivers aged 75+ years in their own vehicles, and (ii) examine the influence of body mass index (BMI), comfort and comorbidities on belt fit and use. Methods: Photographs were taken of drivers in their vehicles to assess belt fit and accessory use. Surveys of comorbidities and belt use, and measurements of height and weight were made. Logistic regression and mediation analysis examined associations between BMI, comfort, comorbidities and belt fit, belt repositioning behaviour, and accessory use. Results: 367 drivers were photographed, mean age 80 years, 23% used an accessory, 47% had poor sash and 41% poor lap belt fit. While 90% reported their belt as comfortable, 21% reported repositioning their belt. Poor lap belt fit was more likley in obese (OR2.2, 95% CI: 1.2–4.0) and overweight drivers (OR 1.8, 95% CI: 1.1–3.0), and females (2.2, 95% CI: 1.3–3.5). Comfort pads were associated with shorter stature (OR 1.1 95% CI: 1.02–1.1), and cushions with belt discomfort (OR 2.5, 95% CI: 1.1–5.6). Musculoskeletal comorbidities increased belt repositioning (OR 1.3, 95% CI: 1.1–1.6), and comfort partially mediated this relationship (p = 0.03). General comorbidities, increased the odds of accesory use (OR 1.2 95% CI: 1.04–1.3). Conclusions: Older drivers face challenges achieving comfortable and correct belt fit, and many reposition belts and use comfort accesories. This may negatively impact crash protection.Older drivers need to be aware of the importance of good belt positioning, particularly those with comorbidities.The impact of accesories on injury risk needs examination.